Internet as a Meeting Place for Spouses: Online Dating, Homogamy and Assortative Mating in Contemporary Italy - Laura Arosio (European Scientific Journal, ESJ, 2022)
In this article places where spouses first met in Italy are studied. The focus is on online settings in the most recent marriage cohorts (2000-2016). The aim is to investigate trends over time of using the Internet as a meeting place and to explore whether Internet dating can affect assortative mating and homogamy rules. Information on first marriages is analysed to study highly committed and long-lasting relationships between partners. Data used for the analyses come from the nationally representative survey "Family, Social Subjects and Life Cycle" carried out by the Italian National Statistical Institute (Istat) in 2016 on a sample of about 32,000 individuals made available in 2020. The results allow a preliminary quantification of the phenomenon and document an increase in meetings occurring online in Italy (from 0.4 per cent in the marriage cohort 2000-2009 to 2.5 per cent  in the marriage cohort 2010-2016). Furthermore, data support the idea that online contexts show homogamy paths not different from those that characterize offline dating venues. Meeting a partner online does not seem to imply heterogamy.